2014
DOI: 10.1175/jpo-d-13-095.1
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Trapped Waves, Alongshore Pressure Gradients, and the California Undercurrent*

Abstract: The California Undercurrent (CUC), a poleward-flowing feature over the continental slope, is a key transport pathway along the west coast of North America and an important component of regional upwelling dynamics. This study examines the poleward undercurrent and alongshore pressure gradients in the northern California Current System (CCS), where local wind stress forcing is relatively weak. The dynamics of the undercurrent are compared in the primitive equation Navy Coastal Ocean Model and a linear coastal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 62 publications
5
90
0
Order By: Relevance
“…A recent study suggested that previously documented benthic 14 C anomalies in core PC08 might be an artifact of tuning the sediment age model to GISP2 age (Davies-Walczak et al, 2014). Following Davies-Walczak et al (2014) we therefore constructed an alternative age model based on an assumption of constant reservoir age in the better equilibrated (younger) planktonic species as measured in the present study.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study suggested that previously documented benthic 14 C anomalies in core PC08 might be an artifact of tuning the sediment age model to GISP2 age (Davies-Walczak et al, 2014). Following Davies-Walczak et al (2014) we therefore constructed an alternative age model based on an assumption of constant reservoir age in the better equilibrated (younger) planktonic species as measured in the present study.…”
Section: Methodsmentioning
confidence: 97%
“…Following Davies-Walczak et al (2014) we therefore constructed an alternative age model based on an assumption of constant reservoir age in the better equilibrated (younger) planktonic species as measured in the present study. The alternative age model only slightly affects the timing and magnitude of the estimated 14 C anomalies in the benthic and other planktic species, while imposing an unlikely sedimentation rate history (see the Online Supplement for details).…”
Section: Methodsmentioning
confidence: 99%
“…These waves directly influence the velocity structure over the shelf, including the surface velocity, as they drive strong (∼0.15 m s −1 ) quasi‐barotropic velocity fluctuations on time periods of 5–10 days [ Battisti and Hickey , ]. Additionally, they influence the alongshore pressure gradient over the slope and thus the CUC [ Connolly et al ., ]. The event‐scale variability in velocity structure over the midshelf mooring, RS (Figure ), shows that our model is properly propagating CTWs from the boundaries.…”
Section: Methodsmentioning
confidence: 99%
“…The CUC is a large‐scale feature that forms over the midlatitude Eastern Pacific Ocean continental slope [ Hickey , ] extending as far north as VI [ Thomson and Krassovski , ; Pierce et al ., ]. In the northern CCS, the CUC has been linked to the alongshore pressure gradient [ Hickey , ; Werner and Hickey , ; Connolly et al ., ]. It typically manifests itself as a depth‐intensified northward current centered below the shelf‐break (∼250–350 m) and is present throughout the summer/fall upwelling season.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have related coastal flow variability in the eastern Pacific to remotely forced CTWs [cf. Connolly et al ., , and references therein]. Shaffer et al .…”
Section: Coastal‐trapped Wavesmentioning
confidence: 99%